Evaluation of Supreme Court Reversal Decisions Based on Forensic Psychiatric Grounds - Depreli, Ahmet; Ataseven, Tuğba; Malkoç, Mehmet Ali (The Bulletin of Legal Medicine, 2023)
Objective: We aimed to gain information about what justice mechanism expects from expert in forensic psychiatric issues and to contribute to literature by examining decisions to reverse Supreme Court based on forensic psychiatric reasons.Methods: Search was made with keywords “Forensic Medicine” and “Annulment” between 15.05.2022-30.05.2022 using Supreme Court Decision Search internet address. 2833 Supreme Court reversal decisions, which were in 2021 and concerning forensic medical issues, were analysed. Due to insufficient data shared in terms of relevant parameters, files evaluated by law offices of Supreme Court were excluded. Among decisions on 1986 file, which were examined by remaining criminal chambers of Supreme Court and general assembly, 280 reversal decisions, in which a forensic psychiatric issue was cited as a reason for reversal, were included in study.Results: In 14% (n=280) of 1986 criminal files examined by Supreme Court in 2021, at least one of reasons for legal reversal was a forensic psychiatric issue. When 280 files were examined, it was determined that first rank was violations within scope of Article 32 of the Turkish Penal Code with 207 files. When files which were decided to be reversed within scope of Article 32 are examined; most common reason (60.8%; n=126 files) was absence of any report. This shows that some people’s mental illnesses may be overlooked during trial process.Conclusion: Scanning standards expected by Court of Cassation on these issues at regular intervals will ensure a healthier progress in judicial process.
Keywords: Forensic Psychiatry; Criminal License; Supreme Court